Analysis of Strength, Weakness, Opportunity and Treath (SWOT) of Gold Savings Products on Customer Satisfaction of PT Pegadaian (Makassar 1 Area) - Santika, Nilan; Modding, Basri; Selong, Abbas (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This research was conducted with the aim to: (1) analyze the Strength, Weakness, Opportunity and Treatment (SWOT) of the Gold Savings Product at PT. Pegadaian Makassar Area 1; (2) examine the effect of Strength Analysis on customer satisfaction; (3) assess the effect of Weakness Analysis on customer satisfaction; (4) evaluate the effect of Opportunity Analysis on customer satisfaction; and (5) investigate the effect of Treath Analysis on customer satisfaction. For this study, 115 individuals from the entire population were given questionnaires to collect primary data using a quantitative technique. The study was carried out at PT. Pegadaian Makassar Area 1, which is located on Jalan Sulawesi No. 285 Butung, Wajo District, Makassar City, South Sulawesi for three months, from October to December of 2023. Multiple linear regression was used in the analytical approach together with the simple random sampling method. The results of this research reported that: (1) The position of Gold Savings products of PT. Pegadaian Makassar Area 1 was in quadrant 1, namely OS (Opportunity, Strength); (2) Analysis of the strength and advantages of gold savings demonstrated a positive and significant effect on customer satisfaction; (3) Weakness analysis/lack of gold savings illustrated a positive and significant effect on customer satisfaction; (4) Opportunity analysis/gold savings opportunities revealed a positive and insignificant effect on customer satisfaction; and (5) Analysis of the threat/threat of gold savings denoted a positive and significant effect on customer satisfaction.